Optimization of distribution network design product frozen food using linear programming - Probokusumo; Sari, Endah Murtiana; Karyadi; Raspati, Galih; Muchsam, Yoki (International Journal of Innovative Research and Scientific Studies, 2025)
Planning logistics costs that are effective and efficient is the goal of the company. Logistics costs need to be modeled through the demand occurring in the market so that the lowest and most efficient logistics cost scenario for the company can be found. This research aims to forecast the logistics costs of CV MIS, an organic food company that produces fresh and beneficial products by mixing antibiotic-free chicken, duck, and fish with probiotics or beneficial bacteria in animal feed and further processing. The consumer locations are scattered across various regions in Indonesia. Through a case study in this company, this research produces the lowest and most efficient scenario using the Mixed Integer Linear Programming (MILP) model, solved using the branch-and-bound technique on Lingo 20 software. The results of this study show that in the 20% demand scenario, the lowest total logistics cost is found in scenario 3 by opening one distribution center (DC) with a capacity of 7,500 Kg, specifically at DC(A), with a total cost of 2.3 billion IDR. In the 40% demand scenario, the lowest total logistics cost is found in scenario 6 by opening 1 DC with a capacity of 7,500 Kg precisely at DC(A) with a total cost of 2.3 billion IDR. In the 80% demand scenario, the lowest total logistics cost is found in scenario 9 by opening one DC with a capacity of 7,500 Kg exactly at DC(A) with a total cost of 2.3 billion IDR. Thus, the number and location of the chosen DC opening is in the Muara Sugihan area, by opening one DC with a capacity of 7,500 Kg. This research will be used as a basis for recommendations to open new routes in South Sumatra by CV Mina Indo Sejahtera, thus achieving effective and efficient logistics costs.